"How Do You Feel about Antibiotics for This?" A Qualitative Study of Physician Attitudes towards a Context-Rich Communication Skills Method - Christopher C. Butler; Geert-Jan Dinant; Eefje G. P. M. de Bont; Fleur H. F. Chappin; Mirjam E. van Leeuwen; Jochen W. L. Cals (MDPI AG, 2013)
To explore experiences with and views of general practitioners (GPs) on a physician communication training method in primary care and its applicability and implementation in daily practice, we performed a semi-structured qualitative study of GPs' experience of training in and implementing a communication skills training program for managing lower respiratory tract infection (LRTI) which included a seminar, simulated patient consultation together with providing and receiving feedback on ones own transcript, and a seminar in a structured approach to the LRTI consultation. Seventeen out of 20 eligible GPs who had participated in the IMPAC3T trial and were allocated to receiving enhanced physician communication training for managing lower respiratory tract infection participated. GPs' experiences with the physician communication training method and its specific components were positive. The method gave GPs additional tools for managing LRTI consultations and increased their sense of providing evidence-based management. During the study, GPs reported using almost all communication items covered in the training, but some GPs stated that the communication skills diluted over time, and that they continued to use a selected set of the skills. The general communication items were most regularly used. Implementation of the method in daily practice helped GPs to prescribe fewer antibiotics in LRTI with the only perceived disadvantage being time-pressure. This study suggests that GPs felt positive about the physician communication training method for enhanced management of LRTI in primary care. GPs continued to use some of the communication items, of which general communication items were the most common. Furthermore, GPs believed that implementation of the communication skills in daily practice helped them to prescribe fewer antibiotics. The context-rich communication method could have wider application in common conditions in primary care.